AN OVERVIEW ON COMMUNITY PHARMACY PRACTICES (International Journal of Food and Nutritional Sciences, 2022)
Community pharmacies, also known as retail pharmacies or drug stores, serve as crucial points of contact between healthcare providers and the general public. They are responsible for dispensing medications, providing medication counseling, and offering over-the-counter products, among other healthcare-related services.Community pharmacies play a vital role in providing essential healthcare services to local communities. There are various aspects of community pharmacy practices including the accessibility, quality of services, availability of medications, professional competence, and adherence to regulatory guidelines.